From Questioning to Answering: The Paranoid Dialectics of P. K. Dick. Issue 4 (2nd October 2019) - Flemming, Gregory C.
Abstract : With reference to the work of American science fiction writer Philip K. Dick and the two Blade Runner films based on his writings, this commentary briefly explores the notion of totality (both closed and open) as it relates to psychoanalysis and politics. Where the original Blade Runner film pointed to a bleak but open universe, the newer film presents one sutured closed, with the promise of making each subject whole. With an eye to Žižek's understanding of ideology, Lacan's take on the "paranoid structure of knowledge, " and P. K. Dick's understanding of totality, it becomes clear that an important aspect of ideology is the move from asking questions to providing answers. Where the former opens up possibilities that have no answers, the latter reduces politics to empirical choice.